3D Printing Customized Optical Lens in Minutes. Issue 4 (4th December 2019) - Shao, Guangbin; Hai, Rihan; Sun, Cheng
Abstract: Synergizing grayscale photopolymerization and meniscus coating processes, rapid 3D printing of optical lenses is reported previously using projection microstereolithography (PµSL) process. Despite its 14 000‐fold‐improved printing speed over the femtosecond 3D printing process, PµSL still consumes significant amount of the fabrication time for precise recoating 5 µm thick fresh resin layers. At the reported speed of 24.54 mm 3 h −1, 3D printing of the millimeter‐size lenses still takes hours. To further improve the printing speed, the microcontinuous liquid interface production process is implemented to eliminate the time‐consuming resin recoating step. However, the micrometer‐size pores in the Teflon membrane needed for oxygen transportation are found to completely spoil the surface smoothness. The use of polydimethylsiloxane thin film possessing much refined nanoscopic porosities as the functional substitute of Teflon membrane is reported to significantly reduce the surface roughness to 13.7 nm. 3D printing of 3 mm high aspherical lens in ≈2 min at a 200‐fold‐improved speed at 4.85 × 10 3 mm 3 h −1 is demonstrated. The 3D printed aspherical lens has the demonstrated imaging resolution of 3.10 µm. This work represents a significant step in tackling the speed‐accuracy trade‐off of 3D printing process and thus enables rapid fabrication of customized optical components. Abstract : Microcontinuous liquid interface production is introduced to accelerate the optical lens 3D printing process. Polydimethylsiloxane membrane is demonstrated to provide a smoother surface finish than the widely used Teflon membrane. In this work, optical lens is printed in ≈2 min and shows the capability to resolve Element 3 in Group 7 of United States Air Force 1951 resolution test chart.